Immigration and income inequality in Sweden - Ronja Grundsten (Luxembourg Income Study (LIS), 2015)
Income inequality has been on the rise in many industrialised countries since around the 1980's. In Sweden the increase of income inequality has been particularly large. This in spite of Sweden's extensive redistribution system and public policy that prioritize equality among its population. This paper investigates a potential factor for the rise in inequality that is yet fairly unexplored, namely immigration. As inequality has increased in Sweden, so has also immigration. Sweden experienced large refugee inflows after the 1970's, the largest flow consisting of circa 100 000 Yugoslavs during the Bosnian war. This study provides indications on what way immigration shapes the income distribution and lays the ground for prospective studies. Results show that the inflow of new migrants during the early 1990's in Sweden raises income inequality and it is almost entirely due to increased dispersion in the lower tail of the income distribution.
Keywords: 330; Income inequality; Disposable income; Immigration; Political refugee; Demographic shifts; Multinomial Probit; Sweden